EVALUASI PENERAPAN PERTANIAN PADI SAWAH SEMI ORGANIK SETELAH MUSIM TANAM V - Jauhari Syamsiyah; Hery Widijanto; Mujiyo Mujiyo (Caraka Tani: Journal of Sustainable Agriculture, 2009)
The study about “Evaluation of semi organic system on rice production at fifth plant season” whose purpose to evaluate the quality and rice yield at semi organic system at fifth plant season, its impact on soil chemistry properties and its properness to farmers. This field experiment has been conducted from May to September 2008 at Palur, Sukoharjo, with two factors. The first factor is anorganic fertilizer at recommendation dose (Urea 300 kg ha-1, ZA 100 kg ha-1, SP-36 150 kg ha-1, KCl 100 kg ha-1). The second factor is 30% of dose recommendation anorganic fertilizer (Urea 100 kg ha-1, ZA 30 kg ha-1, SP-36 50 kg ha-1, KCl 30 kg ha-1) and five tons organic fertilizer. The data was analyzed with T test to evaluate the differences of semi organic system and anorganic system. The experiment’s result shows that the semi organik system gives weight of dry straw which is higher than anorganic system. The yield of dry unhulled rice in semi organic system(9,2 ton/ha) isn’t significantly different from the weight which is compared with anorganic system (8,576 ton/ha). From the economic analysis, semi organic system gives higher profit than anorganic system. The rice quality (dust and fiber contain) in semi organic system is higher but protein contain isn’t different. Semi organik system gives organik matter contain (1,618%), KPK (14,454 cmol/kg), N total (0,368%), available P (0,368 ppm) and available K (164,96 me%) which is signiificantly higher but givew lower pH (5,5) than anorganic system.